Bilateral Congenital Absence of the Femur: A Case Report - Abdalsalam Andisha; Taimaa Langhi (AlQalam Journal of Medical and Applied Sciences, 2025)
Congenital femoral deficiency (CFD) is a rare congenital limb anomaly ranging from mild shortening to complete absence of the femur. Bilateral complete femoral agenesis is exceptionally rare. We report a 3-year-old male born to a 42-year-old mother with poorly controlled type 2 diabetes. At birth, the patient was diagnosed with bilateral complete femoral agenesis, accompanied by multiple anomalies including bilateral clubfoot, cleft palate, congenital heart disease, bilateral cryptorchidism, and inguinal hernia. Radiographs revealed complete femoral absence with tibiae articulating directly with hypoplastic acetabula. The patient underwent bilateral posteromedial release for clubfoot, but recurrence occurred due to difficulty maintaining standard orthotic positioning. The severity and constellation of anomalies suggest a developmental insult during early embryogenesis, likely influenced by maternal metabolic factors. Traditional classification systems do not encompass this presentation, complicating diagnosis and treatment planning. Reconstructive options were not feasible due to the complete absence of femoral shafts; instead, orthopedic care focused on soft-tissue release, early bracing, and planning for prosthetic fitting to improve function. This case emphasizes the importance of maternal health during pregnancy and illustrates the critical role of individualized orthopedic management, including early soft-tissue procedures, custom bracing, and eventual prosthetic adaptation, in optimizing function in patients with severe limb deficiencies. It is the first reported case from North Africa.